Substitution of virginiamycin with yeast-based products (Saccharomyces cerevisiae) in diets of cattle: digestibility and ruminal parameters - dos Santos de Oliveira, Daiana; de Oliveira Moura Silva, Luan; Ribeiro, Laís Gonçalves; de Sousa, Debora Gomes; Pereira, Leidiano Martins; Couto, Victor Rezende Moreira; da Rocha Fernandes, Marcia Helena Machado [UNESP]; Arnhold, Emmanuel; do Nascimento, Mariana Quintino; Manzano, Ricardo Pereira; de Resende Fernandes, Juliano José (FapUNIFESP (SciELO), 2024)
The aim of this study was to evaluate the effect of substituting virginiamycin with yeast-based products in high-energy diets containing monensin on the nutrient digestibility and ruminal parameters of cattle. Five crossbred Nellore × Holstein steers (initial body weight 281 kg ± 9.2 kg) were allotted to a 5 × 5 Latin square design. The diets were composed in dry matter basis of corn silage (355 g kg-1), and concentrate composed of ground corn, soybean meal, soybean hulls,mineral mix, limestone, salt and urea (645 g kg-1). The treatments were: 1 - control, 18 mg kg-1 dry matter (DM) virginiamycin (VM); 2 - enriched yeast culture (Saccharomyces cerevisiae) at 7 g animal day-1 (EYC 7); 3 - enriched yeast culture (S. cerevisiae) at 14 g animal day-1 (EYC 14); 4 - autolyzed yeast (S. cerevisiae) at 7 g animal day-1 (AY 7); and 5 - autolyzed yeast (S. cerevisiae) at 14 g animal day-1 (AY 14). Monensin (18 mg kg-1 DM) was added to the mineral mix in all treatments. No significant differences (P > 0.05) were found for DM intake (mean 8.36 kg DM), organic matter (OM) digestibility (average of 58.39%), or mean ruminal pH (mean 6.75) among treatments. Moreover, the treatment did not have a significant effect on the short-chain fatty acid or ammonia nitrogen concentrations. These results indicated the possibility of replacing virginiamycin with yeast-based products at the lowest level (7 g of enriched yeast culture or autolyzed yeast per animal day-1) in high-energy diets containing monensin.
Substituição de virginiamicina por produtos a base de levadura (Saccharomyces cerevisiae) em dietas de bovinos: Digestibilidade e parâmetros ruminais
Keywords: antibiotics; autolyzed yeast; cattle; enriched yeast culture